PENDIDIKAN MASA DEPAN INDONESIA (ANALISIS SWOT, SOM, INTER DAN MULTIDISIPLINER) - Murjani Murjani (CV. ADIBA AISHA AMIRA, 2022)
The key for Islamic educational institutions to survive in the midst of change is to understand their position, and what is going on, as well as their readiness to be part of a new world that is undergoing change. An Islamic educational institution certainly knows the problems of the institution, knows its strengths, weaknesses, opportunities and threats so that it can produce brilliant solutions and can bring Islamic educational institutions to a very influential position in the scientific struggle of the nation and the world.